2022
DOI: 10.1111/sms.14164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of specific collagen peptide supplementation combined with resistance training on Achilles tendon properties

Abstract: The purpose of this study was to investigate the effect of specific collagen peptides (SCP) combined with resistance training (RT) on changes in tendinous and muscular properties. In a randomized, placebo‐controlled study, 40 healthy male volunteers (age: 26.3 ± 4.0 years) completed a 14 weeks high‐load resistance training program. One group received a daily dosage of 5g SCP while the other group received 5g of a placebo (PLA) supplement. Changes in Achilles tendon cross‐sectional area (CSA), tendon stiffness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 60 publications
3
14
5
Order By: Relevance
“…Although previous studies using high-intensity resistance training for 9–12 weeks found an increase in patellar tendon CSA at the proximal and distal ends ( Kongsgaard et al, 2007 ; Seynnes et al, 2009 ), the intensity of training in the current study was probably insufficient to induce tendon hypertrophy. In contrast to our findings, a recent study by Jerger et al (2022) showed that moderate-to-high intensity strength training (70%–85% single repetition maximum) for 14 weeks with 5 g daily collagen supplementation further increased Achilles tendon CSA compared to training alone in previously untrained, healthy, young men. However, the increase in tendon stiffness after training did not differ between PLA and COL in this study ( Jerger et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Although previous studies using high-intensity resistance training for 9–12 weeks found an increase in patellar tendon CSA at the proximal and distal ends ( Kongsgaard et al, 2007 ; Seynnes et al, 2009 ), the intensity of training in the current study was probably insufficient to induce tendon hypertrophy. In contrast to our findings, a recent study by Jerger et al (2022) showed that moderate-to-high intensity strength training (70%–85% single repetition maximum) for 14 weeks with 5 g daily collagen supplementation further increased Achilles tendon CSA compared to training alone in previously untrained, healthy, young men. However, the increase in tendon stiffness after training did not differ between PLA and COL in this study ( Jerger et al, 2022 ).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, a recent study by Jerger et al (2022) showed that moderate-to-high intensity strength training (70%–85% single repetition maximum) for 14 weeks with 5 g daily collagen supplementation further increased Achilles tendon CSA compared to training alone in previously untrained, healthy, young men. However, the increase in tendon stiffness after training did not differ between PLA and COL in this study ( Jerger et al, 2022 ). The discrepancies between our findings and those of Jerger et al (2022) are likely linked to the numerous methodological differences between studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…They demonstrated that collagen peptide supplementation yielded significantly greater tendon and plantar flexor cross-sectional area compared with controls. However, tendon stiffness and muscular strength improved similarly in both groups with resistance training [22]. These increases in tendinous tissue synthesis when combined with a resistance or rehabilitative program may also enhance recovery from injury via improved collagen production.…”
Section: Strength and Body Compositionmentioning
confidence: 80%